(untitled) (Colombia Medica, 1981)
The aim of this essay is to discuss pain, which is considered a state of illness that alters human capacity. It analyzes the physician’s position in front of pain and its dramatic dimension, and it criticizes some proposals that have been made on modifying the therapeutic relationship. As for criticisms made to medical specialization, it considers the problem to lie in the connection between a strict cognitive specialization and decisions made in therapeutic practice. This problem is deeply related to the role played by medical training and practice in social life.